ANALYSIS IN THE EPICS "MAHZAN UL-ASROR" AND "MAJMA'UL-AKHBAR" - Shakhnoza Karimova (Journals Park Publishing, 2022)
The article analyzes for the first time the "Majma'ul-axbor" epic of Sayyid Qasimi, who has not been practically studied in Uzbek literature, from a comparative perspective with the "Makhzan ul-Asror" epic of Nizami Ganjavi, comparing the plot features of the construction of compositions of dostons, studying the common and different aspects in them. In order to reveal the topic of the article, scientific works of medieval literary critics and new period literary critics were used..
Keywords: composition